(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
Solid Works, a comprehensive 3D CAD design solution, equips the product design team with all the necessary tools for mechanical designs, verifications, motion simulations, data management, and communication. This paper delves into Solidworks as a pedagogical simulation software, a practical tool that can significantly enhance the mechanical design skills of mechanical engineering students at the National Institute of Construction Technology and Management, Edo State, Nigeria. The study was structured as an educational design experiment, utilizing Solidworks to teach design concepts. Two equivalent groups were formed; one was the experimental group, and the other was the control group. Both groups were given the same project, with the first group using SW-P and the second group using the traditional method. The results showed that Solidworks is an efficient method for enhancing mechanical design skills. Students using Solidworks demonstrated a deeper understanding of the design concepts, surpassing those using the traditional method.